TI_GERICHTE 11.2014.28 vom 7. Juni 2016 , Risarcimento del danno per impossibilità di esercitare un usufrutto - TI Tribunale d'appello (2016)
Risarcimento del danno per impossibilità di esercitare un usufrutto